(untitled) (Research, Society and Development, 2021)
The intestinal microbiota influences important local and systemic processes for the organism, having in its composition probiotic bacteria that assist in the beneficial processes and commensal bacteria, which often cause infections. The aim of this article is to analyze the existence of a relationship between the prevalence of pathogenic bacteria and intestinal inflammation when plasma levels are deficient in vitamin D. For this, a literature review was carried out with a systematic search in order to capture the current information. on the topic, in order to contribute to the clinical direction. As a result of the analysis, it was found that vitamin D sufficiency favors the presence of probiotics and intestinal barrier integrity, and that deficiency is associated with the prevalence of pathobionts and intestinal inflammation. Therefore, maintaining sufficient serum levels of vitamin D favors intestinal health, enabling an enterotype dominated by probiotics, decreasing inflammatory markers and protecting the integrity of the intestinal barrier.